Drug-Resistant Tuberculosis Stigma Among HealthCare Workers Toward the Development of a Stigma-Reduction Strategy: A Scoping Review - Lolita Liboon Aranas DPA; Khorshed Alam PhD; Prajwal Gyawali PhD; Rashidul Mahumud Alam PhD (Inquiry: The Journal of Health Care Organization, Provision, and Financing, 2023)
Drug-resistant tuberculosis (DRTB) is a growing concern worldwide. The poor rate of service delivery exacerbates the severity, leading to an increase in community transmission, which is further amplified by stigma. Health care workers (HCWs) are at the forefront lines of service delivery; their efforts are suspected of resulting in stigmatization, negatively impacting patient-centered care. However, little is known about DRTB-related stigma among these HCWs, and interventions are limited. Our scoping review is significant because it provides an overview of the DRTB stigma confronting HCWs and informs subsequent stigma-reduction initiatives. Utilizing Arksey and O’Malley framework, we exhaustively searched electronic databases for relevant English-language studies published from 2010 to 2022, identifying the drivers and facilitators of DRTB-related stigma among HCWs from high-TB and -DRTB burden countries, and compiling recommendations that could reduce DRTB stigma. From 443 de-duplicated papers, 11 articles on HCWs’ DRTB-related stigma were reviewed and synthesized. Fear was mentioned across included articles as a stigma driver. Other reported stigma drivers identified included feelings of discrimination, isolation, danger, lack of support, shame, and stress. Poor infection control (IC) was the leading stigma facilitator. Other stigma facilitators identified were differing IC interpretations, workforce culture, and workplace inequality facilitating to stigmatization of HCWs. Three key recommendations identified were addressing infection control issues; increase the competence of healthcare workers; and provide psychosocial assistance, emphasizing HCW safety during DRTB activities. DRTB stigma among HCWs is multifaceted, largely driven by fear and facilitated by varying implementation or interpretations of policies within the workplace. Making HCWs feel safe while conducting DRTB activities is a priority issue that should be addressed by improving IC, training and psychosocial support. More studies investigating country-specific and multilevel DRTB-related stigma among HCWs are required to inform the development of an effective stigma intervention strategy.